Local Knowledge in the Digital Age: Developing an E-Module on Bali Tribe's Traditional Medicinal Plants in Tawang Rejo Village for Class X - Nurhidayah, Muhammad Gading; Jumiarni, Dewi; Yennita, Yennita (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2024)
The electronik modul (e-module) is a digital learning resource designed to enhance the educational experience. However, at SMA 06 Seluma, there is a noticeable lack of electronic teaching materials, particularly those based on local environmental content, like biodiversity. This study aims to develop a biodiversity e-module that draws from the surrounding environment. The development process followed the 4-D model, which includes four stages: defining, designing, developing, and disseminating. The research involved interviews and observations of medicinal plants. The findings identified 37 species of medicinal plants across 22 families utilized by the Bali tribe in Tawang Rejo Village. Validation results for the e-module were positive: content experts rated it 92%